2021
DOI: 10.1007/s00382-021-05963-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclonic activity in the Mediterranean region from a high-resolution perspective using ECMWF ERA5 dataset

Abstract: This study focuses on developing a new Cyclone Detection and Tracking Method (CDTM) to take advantage of the recent availability of a high-resolution reanalysis dataset of ECMWF ERA5. The proposed algorithm is used to perform a climatological analysis of the cyclonic activity in the Mediterranean Region (MR) into a 40-year window (1979–2018). The tuning of the new CDTM was based on the comparison with currently available CDTMs and verified through careful subjective analysis to fully exploit the finer details … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…Cyclones mostly formed at 0000 UTC (45%) followed by a secondary peak at 1200 UTC (32.5%). These characteristics are in agreement with previous studies on western Iran's cyclones (Bayat et al ., 2017) and Mediterranean cyclones (Trigo et al ., 1999; Trigo et al ., 2002; Lionello et al ., 2006; 2016; Campins et al ., 2010; Flaounas et al ., 2016; 2018b; 2019; 2021a; Aragão and Porcù, 2021). These studies showed that overall, the average lifetime of these cyclones is 1 day and that they mostly formed in the eastern Mediterranean region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclones mostly formed at 0000 UTC (45%) followed by a secondary peak at 1200 UTC (32.5%). These characteristics are in agreement with previous studies on western Iran's cyclones (Bayat et al ., 2017) and Mediterranean cyclones (Trigo et al ., 1999; Trigo et al ., 2002; Lionello et al ., 2006; 2016; Campins et al ., 2010; Flaounas et al ., 2016; 2018b; 2019; 2021a; Aragão and Porcù, 2021). These studies showed that overall, the average lifetime of these cyclones is 1 day and that they mostly formed in the eastern Mediterranean region.…”
Section: Resultsmentioning
confidence: 99%
“…First according to the study of Sainsbury et al . (2020), we averaged the 850 hPa relative vorticity and mean sea level pressure 1‐hourly ERA5 data into 6‐hourly intervals and resampled their spatial resolution from 0.25° to 0.75° because 6‐hourly data can better describe cyclone identification and deepening over the Mediterranean region (Aragão and Porcù, 2021). We identified the cyclones in the domain of 12°–42°N and 15°–60°E as follows: The relative vorticity at the cyclone centre and its eight surrounding neighbour grid points must be greater than 3 × 10 −5 s −1 . The local maximum of the relative vorticity at the cyclone centre must be greater than its eight surrounding neighbour grid points. The cyclone centre location must have lower mean sea level pressure than that of the eight neighbouring grid points. The cyclones must have a lifetime of at least 1 day. The tracking of the cyclones was performed over a domain with a range of 10° longitude and 5° latitude. If there are multiple cyclones in the domain, we choose the cyclone centre with the maximum relative vorticity and lowest mean sea level pressure. …”
Section: Methodsmentioning
confidence: 99%
“…ERA5's reanalysis benefits from ten years of improvements over the previous one; ERA-Interim (Dee et al, 2011), mainly in the physics model, dynamics, and data assimilation, in addition to the more refined spatial resolution (Hersbach et al, 2020). Recent studies with different objectives and applied to different regions have utilized this newer reanalysis, for example, Gramcianinov et al (2020), Aragão andPorcù (2022), andPezzi et al (2022). Satellite data from the Geostationary Environmental Satellite (GOES-16) were also used in the infrared (channel 13 -10.36 μm) and water vapor (channels 7, 8, and 9 -6.2 μm; 6.9 μm; 7.3 μm for high, medium and low levels, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Cyclones are a crucial component in the dynamics of the atmosphere. They develop where the flow favors their growth and play a fundamental role in the hydrological cycle since they carry heat, humidity, and momentum (Peixoto and Oort, 1992;Wallace and Hobbs, 2006;Reboita et al, 2010;Gertler and O'Gorman, 2019;Gramcianinov et al, 2019;Reale et al, 2019;Aragão and Porcù, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We compute backward trajectories using LAGRANTO (Wernli and Davies, 1997;Sprenger and Wernli, 2015) until 48 h prior to the mature stage of the cyclone (−48 h), which is an adequate time period considering the short life span of Mediterranean cyclones (Trigo et al, 1999;Aragão and Porcù, 2022). Along these, we trace surface pressure, PV, and in the IFS simulations the available PV rates due to different diabatic processes.…”
Section: Lagrangian Perspective On Diabatic Pv Modificationmentioning
confidence: 99%